Comparison Of Psychological Conditions Of Career Murability Of Man Students With High School Students In Tanah Datar District - Yuliani, Tri (Batanang : Jurnal Psikologi, 2022)
This discussion starts from the problem, namely how to compare the career maturity of MAN students with high school students. Career maturity is the level at which individuals have mastered the tasks of career development, both knowledge and attitude components, which are in accordance with the stage of career development and career maturity is also an individual's ability to make the right career choices, including awareness of what is needed to make career decisions and level of career development. where individual choices are realistic and consistent. This study aims to determine and obtain data about the career maturity of MAN students and high school students, so whether there is a difference in career maturity between MAN students and high school students. The population of this research is SMA and MAN in Tanah Datar, the samples are MAN 2 Batusangkar and SMA 1 Pariangan. By taking samples at these schools by means of cluster random sampling, from the sampling, the samples were selected for local class X 1, class XI 1 local and class XII 1 local each school with a sample of 179 students. The type of research used is comparative descriptive by analyzing the differences in career maturity of MAN students and high school students. The measurement of career maturity is by using a questionnaire consisting of 43 statement items, with 4 answer choices. Data were analyzed using the "t" test. From the results of the study using the "t" test formula, it can be seen that the career maturity of the students of MAN 2 Batusangkar is higher than the career maturity of the students of SMA 1 ParianganKeywords: Psychological state, Career maturity, students